Treatment of late-life insomnia - Lichstein, Kenneth L.; Morin, Charles M. (Sage Publications, 2000)
"As the proportion of Americans over the age of 65 steadily increases, so too does the importance of understanding the special health needs of this age group. In the past decade, there has been a great deal of clinical research directed toward the development of effective treatment of insomnia among older adults. Methods of assessment have been developed and key diagnostic issues have crystallized. This book brings together articles from leading researchers in the field, providing a comprehensive state of the art book of great interest to health care professionals."--Jacket